Intensity-Modulated Radiation Therapy with Stereotactic Body Radiation Therapy Boost for Unfavorable Prostate Cancer: A Report on 3-Year Toxicity - Paydar, Ima; Pepin, Abigail; Cyr, Robyn A.; King, Joseph; Yung, Thomas M.; Bullock, Elizabeth G.; Lei, Siyuan; Satinsky, Andrew; Harter, K. William; Suy, Simeng; Dritschilo, Anatoly; Lynch, John H.; et al. (Frontiers in Oncology, 2017)
Background Recent data suggest that intensity-modulated radiation therapy (IMRT) plus brachytherapy boost for unfavorable prostate cancer provides improved biochemical relapse-free survival over IMRT alone. Stereotactic body radiation therapy (SBRT) may be a less invasive alternative to brachytherapy boost. Here, we report the 3-year gastrointestinal (GI) and genitourinary (GU) toxicities of IMRT plus SBRT boost. Materials and methods Between March 2008 and September 2012, patients with prostate cancer were treated with robotic SBRT (19.5 Gy in three fractions) followed by fiducial-guided IMRT (45–50.4 Gy) on an institutional protocol. Toxicity was prospectively graded using the common terminology criteria for adverse events version 4.0 (CTCAEv.4) at the start of and at 1- to 6-month intervals after therapy. Rectal telangiectasias were graded using the Vienna Rectoscopy Score (VRS). Results At a median follow-up of 4.2 years (2.4–7.5), 108 patients (4 low-, 45 intermediate-, and 59 high-risk) with a median age of 74 years (55–92) were treated with SBRT plus IMRT, with 8% on anticoagulation and an additional 48% on antiplatelet therapy at the start of therapy. The cumulative incidence of late ≥grade 2 GI toxicity was 12%. Of these, 7% were due to late rectal bleeding, with six patients requiring up to two coagulation procedures. One patient with rectal telangiectasias was treated with hyperbaric oxygen (grade 3 toxicity). No rectal fistulas or stenoses were observed. Ten patients had multiple non-confluent telangiectasias (VRS grade 2), and three patients had multiple confluent telangiectasias (VRS grade 3). The cumulative incidence of late grade 3 GU toxicity was 6%. Most late toxicities were due to hematuria requiring bladder fulguration. There were no late ≥grade 4 GU toxicities. Conclusion Rates of clinically significant GI and GU toxicities are modest following IMRT plus SBRT boost. Future studies should compare cancer control, quality of life, and toxicity with other treatment modalities for patients with high-risk prostate cancer.